Hospital outcomes in Jehovah’s Witness patients with acute gastrointestinal bleeding: A matched cohort study - Taraji 1; Porsha Okiye; Chakravarthy Nulu; Rithvick Kumar; Andrew Bouffler; Ali Mirza; Vishnavi Batchu; Amit Hudgi; Humberto Sifuentes; Raguraj Chandradevan (Journal of Clinical and Translational Research, 2026)
Background: Acute gastrointestinal bleeding (GIB) may require urgent resuscitation, endoscopy, and red blood cell (RBC) transfusion. Management is particularly challenging in Jehovah’s Witness (JW) patients who decline RBC transfusion. Aim: To compare short-term hospital outcomes between JW patients with acute GIB and individually matched transfusion-eligible comparators. Methods: We conducted a single-center retrospective matched cohort study of adults admitted from 2010 to 2026. Twenty-two JW patients who declined RBC transfusion and underwent inpatient endoscopy were manually matched 1:1 with comparators admitted within 7 calendar days, managed by the same attending gastroenterologist, and meeting the applicable high-risk threshold of Glasgow–Blatchford Score > 6 for suspected upper GIB or Oakland Score > 8 for suspected lower GIB. Paired t-tests or Wilcoxon signed-rank tests were used as appropriate. Results: Mean initial hemoglobin was 8.45 g/dL in JW patients and 9.06 g/dL in comparators (paired difference, −0.61 g/dL; 95% CI, −2.81 to 1.58; p = 0.567). Mean hemoglobin at endoscopy was 8.35 and 9.24 g/dL, respectively (paired difference, −0.89 g/dL; 95% CI, −2.54 to 0.75; p = 0.273). Admission-to-procedure time did not differ significantly (p = 0.472). Median hospital length of stay was 5.5 versus 3.5 days and was longer among JW patients (p = 0.020). Conclusion: No statistically significant differences were detected in hemoglobin outcomes or procedure timing, but JW patients had longer hospital stays. Findings are exploratory and limited by the small sample, residual imbalance, and unavailable patient-level severity scores. Relevance for Patients: Patients with acute GIB who decline RBC transfusion may benefit from individualized monitoring, blood-conservation strategies, and careful discharge planning.